(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Deploying a writing that gives an account of a knowing and of an analysis about the event and its consequences on the ontological plane and therefore on the artistic level, makes it necessary to work on some concepts, in order to appropriate actions that we go through in our research proposal. It is therefore a question of reading writings that give us visibility on the limits and creative possibilities of the fabulation. Initially we approached the concept of event, this lens brings us closer to the power of fabulation and the way it generates acts of resistance against the cultural project of modernity that allow us to summon a participatory artistic act from the image: Call a people